STUDY OF MAGNETOSTRICTIVE PROPERTIES OF MATERIALS BY MEANS OF METHOD OF ATOMIC FORCE MICROSCOPY - D. A. Stepanenko; K. A. Bogdanchuk; V. T. Minchenya; T. A. Kuznetsova (Приборы и методы измерений)
The article studies and experimentally proves possibility of application of atomic force microscope for measurement of small magnetostrictive deformations of materials. Exemplary results of measurements for the samples made of technically pure nickel exhibiting strong magnetostrictive effect are presented.